Correlation Between Serum and Seminal Leptin and Nitric Oxide (Nitrite) in Asthenote-ratozoospermic Males - Nastaran Azarbarz; Parvindokht Bayat; Farideh Jalali Mashayekhi; Ali Asghar Ghafarizadeh; Mohammad Bayat (Negah Institute for Scientific Communication, 2019)
Introduction: Leptin is a critical metabolic signal linking nutrition and reproductive functions. Leptin receptors are expressed in germ cells, Sertoli and Leydig cells. Oxidative stress increases sperm DNA damages. Nitric oxide is a free radical, produced by most cells via Nitric Oxide (NO) synthase and plays stimulatory and inhibitory roles on cells. Physiological concentrations of NO are essential for the biology and physiology systems. However, a low level of NO has a detrimental effect on cells. This study aimed to determine the correlation between seminal and serum leptin and NO in asthenoteratozoospermic men. Methods: Semen and blood samples were obtained from (n=52) males referring to the Arak Infertility Clinic, in Arak City, Iran. We examined each patient for serum hormones (LH, testosterone) by chemiluminescence. Serum and seminal leptin were measured by ELISA and seminal NO was measured by Griess reaction.  Results: There were differences in serum leptin levels, and total testosterone, LH, and NO concentrations among the 2 groups. Asthenoteratozoospermic groups showed higher testosterone and LH levels than the normozoospermic group. Serum leptin levels of asthenoteratozoospermic men significantly increased in comparison with normozoospermic men. Seminal leptin levels of asthenoteratozoospermic men significantly decreased compared to normozoospermic men. NO levels in asthenoteratozoospermic men significantly decreased in comparison with normozoospermic cases. There were no significant correlations between serum and seminal leptin and seminal plasma NO. Conclusion: Our results do not support the hypothesis that in vivo serum and seminal leptin affect NO synthesis. Also, our results revealed that nitrite in the seminal plasma is not able to entirely indicate in vivo NO synthesis.